FGF21 (Fibroblast Growth Factor 21) Defines a Potential Cardiohepatic Signaling Circuit in End-Stage Heart Failure. (6th December 2021) - Sommakia, Salah; Almaw, Naredos H.; Lee, Sandra H.; Ramadurai, Dinesh K.A.; Taleb, Iosif; Kyriakopoulos, Christos P.; Stubben, Chris J.; Ling, Jing; Campbell, Robert A.; Alharethi, Rami A.; Caine, William T.; Navankasattusas, Sutip; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Extrinsic control of cardiomyocyte metabolism is poorly understood in heart failure (HF). FGF21 (Fibroblast growth factor 21), a hormonal regulator of metabolism produced mainly in the liver and adipose tissue, is a prime candidate for such signaling. Methods: To investigate this further, we examined blood and tissue obtained from human subjects with end-stage HF with reduced ejection fraction at the time of left ventricular assist device implantation and correlated serum FGF21 levels with cardiac gene expression, immunohistochemistry, and clinical parameters. Results: Circulating FGF21 levels were substantially elevated in HF with reduced ejection fraction, compared with healthy subjects (HF with reduced ejection fraction: 834.4 [95% CI, 628.4–1040.3] pg/mL, n=40; controls: 146.0 [86.3–205.7] pg/mL, n=20, P =1.9×10 −5 ). There was clear FGF21 staining in diseased cardiomyocytes, and circulating FGF21 levels negatively correlated with the expression of cardiac genes involved in ketone metabolism, consistent with cardiac FGF21 signaling. FGF21 gene expression was very low in failing and nonfailing hearts, suggesting extracardiac production of the circulating hormone. Circulating FGF21 levels were correlated with BNP (B-type natriuretic peptide) and total bilirubin, markers of chronic cardiac and hepatic congestion. Conclusions: Circulating FGF21 levels are elevated in HF with reduced ejection fraction and appear to bind to the heart. The liver is likely the main extracardiac source. This supports a model of hepatic FGF21 communication to diseased cardiomyocytes, defining a potential cardiohepatic signaling circuit in human HF.